Perception of Caregiving During Childhood is Related to Later Executive Functions and Antisocial Behavior in At-Risk Boys - Harwood-Gross, Anna; Lambez, Bar; Feldman, Ruth; Rassovsky, Yuri (Frontiers in Psychiatry, 2020)
Executive functions are considered essential for effective navigation in the social world. Parental responsiveness leading to secure attachment is a critical ingredient for normative social development and, as such, may be connected with executive functions. The purpose of this study was to evaluate whether attachment to mother and patterns of caregiving experienced in childhood predicted later executive function development in at-risk adolescents. Seventy-one adolescent boys were recruited from two high-schools for adolescents who were not deemed suitable for regular schooling due to behavioral and emotional issues. Executive functions were tested using a computer-administered neuropsychological battery (CANTAB), and mother-child attachment patterns and antisocial behaviors were assessed using retrospective and current questionnaires. Structural equation modeling (SEM) approach was employed to examine whether executive functions mediated the relationship between patterns of early maternal care and subsequent development of antisocial behaviors. Although maternal care had a significant direct effect on executive function (standardized coefficient = .49, p < .05) and antisocial behavior (standardized coefficient = .53, p < .05), SEM demonstrated no mediating relationships among these variables. Instead, maternal care predicted unique variance in both executive functions (standardized coefficient = .61, p < .05) and antisocial behavior (standardized coefficient = .51, p < .05). This study suggests a link between the experience of childhood caregiving and adolescent executive functions and delinquency and highlights the importance of early parenting interventions to aid executive function development. Such early interventions could potentially enhance long-term pro-social behavior.